Comparative Transcriptome Analysis Reveals the Biocontrol Mechanism of Bacillus velezensis F21 Against Fusarium Wilt on Watermelon - Jiang, Chun-Hao; Yao, Xie-Feng; Mi, Dan-Dan; Li, Zi-Jie; Yang, Bing-Ye; Zheng, Ying; Qi, Yi-Jun; Guo, Jian-Hua (Frontiers in Microbiology, 2019)
The watermelon (Citrullus lanatus) is one of the most important horticultural crops for fruit production worldwide. However, the production of watermelon is seriously restricted by one kind of soilborne disease, Fusarium wilt, which is caused by Fusarium oxysporum f. sp.niveum (Fon). In this study, we identified an efficient PGPR strain B. velezensis F21, which could be used in watermelon production for Fon control. The results of biocontrol mechanisms showed that B. velezensis F21 could suppress the growth and spore germination of Fon in vitro. Moreover, B. velezensis F21 could also enhance plant basal immunity to Fon by increasing the expression of plant defense related genes and activities of some defense enzymes, such as CAT, POD and SOD. To elucidate the detailed mechanisms regulating B. velezensis F21 biocontrol of Fusarium wilt in watermelon, a comparative transcriptome analysis using watermelon plant roots treated with B. velezensis F21 or sterile water alone and in combination with Fon inoculation was conducted. The transcriptome sequencing results revealed almost one thousand ripening-related differentially expressed genes (DEGs) in the process of B. velezensis F21 triggering ISR (Induced systemic resistance) to Fon. In addition, the Gene Ontology (GO) classification and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment indicated that numerous of transcription factors (TFs) and plant disease resistance genes were activated and validated by using quantitative real-time PCR (qRT-PCR), which showed significant differences in expression levels in the roots of watermelon with different treatments. In addition, genes involved in the MAPK signaling pathway and phytohormone signaling pathway were analyzed, and the results indicated that B. velezensis F21 could enhance plant disease resistance to Fon through the above related genes and phytohormone signal factors. Taken together, this study substantially expands transcriptome data resources and suggests a molecular framework for B. velezensis F21 inducing systemic resistance to Fon in watermelon. In addition, it also provides an effective strategy for the control of Fusarium wilt in watermelon.